Minat Member Sepak Bola Mini Lapangan Volta di Kota Palembang (Jurnal Insan Pendidikan dan Sosial Humaniora, 2024)
The aim to be achieved in this research is to find out how much interest there is in the members of the Volta mini soccer field in the city of Palembang. This research is quantitative descriptive research, with the method used is a survey with data collection techniques using questionnaires or questionnaires. The subjects in this research were the interests of the mini volta field soccer members in the city of Palembang, totaling 96 members. The analysis technique used is in the form of percentages. Based on research that has been carried out on the two factors studied, including intrinsic factors and extrinsic factors, there are the same results from both factors. For the overall results, it was found that the results included in the very high category amounted to 47 or 48.5%, those included in the high category amounted to 47 people or 48.5%, those included in the low category amounted to 1 person or 1% and those included in the very low category amounted to 1 or 1%. So it can be seen from all the results obtained from the data that it has a very high category with a percentage of 85% of the 96 members who filled out the questionnaire.